Atypical manifestations of dengue - Vasantha Kamath; Buvana Radhakrishnan; Kushal Markanday (Wolters Kluwer Medknow Publications, 2022)
Dengue is a major concern in India. It has a diverse spectrum of atypical manifestations across the various systems of the human body with significant mortality and morbidity rates. The following review emphasizes on the various systemic manifestations, including the need for their early recognition and treatment.